Characteristic of paddy farmer in Sg. Burung, IADA Barat Laut, Selangor - Armugam, Kritharan (2015)
Rice is a staple food in Malaysia. The increase in population demands more food supply. However, limited planting areas require high yielding rice. In the rice industry, a paddy farmer must have the positive characteristics such as attitudes and practices that enable increased yield. The paddy yield in IADA Northwest is higher compared to other rice granary. This may be due to the differences in characteristics of paddy farmer and the rice granary compared to other granary. This research is done to study about characteristic farmer in Sg.Burung. 57 respondents are chosen to complete this study. The methods used to collect results include questionnaire, real test, and data analysis and interview. Statistical Package for Social Science (SPSS) version 21 is used to analyze the data which is descriptive data to fulfill the objectives.The conclusion of the study was that the characteristic of the respondents in this area are information seeker, problem solver, willing to invest, have wide network of contact, decision maker, and disciplined. The respondents in Sg. Burung are found to possess high level of the characteristic mentioned and moderate level of risk taking. Hence suitable extension programs for officers and farmers should be implemented to increase their capability and positive attitude in order to increase yield.